Studies on genetic divergence for fruit yield in Abelmoschus esculentus (L.) Moench.] genotypes under coastal eco-system - N. Senthilkumar, S. Mudhalvan, (Journal of Plant Stress Physiology)
A study was conducted for identifying the genetic divergence in okra (Abelmoschus esculentus (L.) Moench) genotypes. Fifteen genotypes were evaluated with the objective of selecting superior genotypes namely, Arka Anamika, Varsha Upahar, Thunder, Dhanya, Pusa-7, Basanthi, S-51, Thanvi-66, CO-2, Akshaya, N-U-Lakshmi, Namadhri, PHS, Villupuram Local, and Karur Local for fruit yield traits. The degree of divergence among 15 genotypes was computed using Mahalanobis’ D2 analysis to assess the genetic diversity. For this programme, morphological characters viz., days to first flowering, plant height, inter node distance, days to fruit maturity, number of immature seeds per fruit, fruit length, fruit girth, number of branches per plant, number of fruits per plant, fruit weight, and fruit yield per plant were studied. Analysis of variance for 15 genotypes of bhendi revealed that all the genotypes were significantly differed among themselves for all the eleven traits studied. The results revealed that the mean performance for fruit yield per plant was maximum in the genotype namely Basanthi(465 g), followed by Dhanya(438 g), and S-51(433 g). The genotypes which recorded high mean performance for fruit yield per plant also exhibited significant per se performance for the traits namely inter node distance, number of fruits per plant and average fruit weight.